Seismic Bearing Capacity of Strip Footings on Cohesive Soil Slopes by Using Adaptive Finite Element Limit Analysis - Weihua Luo; Minghua Zhao; Yao Xiao; Rui Zhang; Wenzhe Peng (Advances in Civil Engineering)
By employing adaptive finite element limit analysis (AFELA), the seismic bearing capacity of strip footing on cohesive soil slopes are investigated. To consider the earthquake effects, the pseudostatic method is used. The upper and lower bounds for the seismic bearing capacity factor (Nce) are calculated, and the relative errors between them are found within 3% or better by adopting the adaptive mesh strategy. Based on the obtained results, design tables and charts are provided to facilitate engineers use, and the effects of footing position, undrained shear strength, slope angle, slope height, and pseudostatic acceleration coefficient are studied in detail. The collapse mechanisms are also discussed, including overall slope failure and foundation failure.